POLITICS AT THE MUSEUM: THE APPEARANCES OF MUSEUM SONOBUDOYO AND MONUMEN YOGYA KEMBALI, YOGYAKARTA - Sektiadi (BRIN, 2011)
Museum was a man-made thing, a culture. This situation made the museum polluted with many tension, especially for the museum founded or managed by the government. This paper tried to evaluate the appeareance of the State Museum of DIY